First record of Meloidogyne incognita on maize (Zea mays L.) in western highland, Vietnam - Mai Linh, Le Thi; Duyen, Nguyen Thi; Tien, Nguyen Huu; Phap, Trinh Quang (Academia Journal of Biology, 2016)
The root-knot nematodes, Meloidogyne incognita, is one of the most important pest on many crops, such as coffee, pepper, vegetables, etc. Firstly, the root-knot nematode populations were collected on corn in Krong Nang (Dak Lak province) and analyzed in comparision with other root-knot nematodes on morphology, ITS sequencing and specific primers. The results confirmed that the corn root-knot nematode population is M. incognita species. The study also added variations of different M. incognita populations on different host plants in the morphological characteristics. PCR product with specific primers for M. incognita is 1000 bp. The genetic diversity based on ITS-rDNA sequencing the M. incognita populations, and between populations of M. incognita, M. javanica and M. arenaria were very low. Citation: Le Thi Mai Linh, Nguyen Thi Duyen, Nguyen Huu Tien, Trinh Quang Phap, 2017. First record of Meloidogyne incognita on maize (Zea mays L.) in western highland, Vietnam. Tap chi Sinh hoc, 39(1): 15-23. DOI: 10.15625/0866-7160/v39n1.7229. *Corresponding author: tqphap@yahoo.com. Received 3 October 2015, accepted 20 March 2017